The ALS-FTD-linked gene product, C9orf72, regulates neuronal morphogenesis via autophagy. Issue 5 (4th May 2019) - Ho, Wan Yun; Tai, Yee Kit; Chang, Jer-Cherng; Liang, Jason; Tyan, Sheue-Houy; Chen, Song; Guan, Jun-Lin; Zhou, Huilin; Shen, Han-Ming; Koo, Edward; Ling, Shuo-Chien
ABSTRACT: Mutations in C9orf72 leading to hexanucleotide expansions are the most common genetic causes for amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). A phenotype resembling ALS and FTD is seen in transgenic mice overexpressing the hexanucleotide expansions, but is absent in C9orf72 -deficient mice. Thus, the exact function of C9orf72 in neurons and how loss of C9orf72 may contribute to neuronal dysfunction remains to be clearly defined. Here, we showed that primary hippocampal neurons cultured from c9orf72 knockout mice have reduced dendritic arborization and spine density. Quantitative proteomic analysis identified C9orf72 as a component of the macroautophagy/autophagy initiation complex composed of ULK1-RB1CC1-ATG13-ATG101. The association was mediated through the direct interaction with ATG13 via the isoform-specific carboxyl-terminal DENN and dDENN domain of C9orf72. Furthermore, c9orf72 knockout neurons showed reduced LC3-II puncta accompanied by reduced ULK1 levels, suggesting that loss of C9orf72 impairs basal autophagy. Conversely, wild-type neurons treated with a ULK1 kinase inhibitor showed a dose-dependent reduction of dendritic arborization and spine density. Furthermore, expression of the long isoform of human C9orf72 that interacts with the ULK1 complex, but not the short isoform, rescues autophagy and the dendritic arborization phenotypes of c9orf72 knockout neurons. Taken together, our data suggests that C9orf72 has a cell-autonomous role in neuronal and dendritic morphogenesis through promotion of ULK1-mediated autophagy.